(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The Fibonacci arrangements of numbers as well as the related "Golden Ratio" shown in nature and certain masterpieces. This paper aims to prove that the “Power of Math” can be found with “Fibonacci Numbers”. Fibonacci can be found in nature in the renowned bunny explore as well as in lovely blossoms. On the highest point of sunflower and seeds are squeezed in light of a particular objective so they track the case of Fibonacci plan. Since Fibonacci numbers has a main role in any individual’s day-to-day life. One can see that a large number of regular things that follows Fibonacci succession. Apparently in natural situations like expanding in plants, phyllotaxis i.e., the way of arrangement of leaves, and organic thing fledglings of uncurling plant, and the game design of pinecone’s bracts, and so on. At present Fibonacci numbers assumes a vital part in the coding hypothesis. Fibonacci numbers are in various structures and broadly applicable in developing security coding. The Fibonacci series can be used in improving the security of communication in the future.